Students’ Bullying Experiences at University Level - Deasyanti, Deasyanti; Muzdalifah, Fellianti (Psikopedagogia, 2021)
Bullying in the context of the university is crucial to be studied as the impact of bullying on students’ well-being. This paper focuses on the issue of bullying at one university in Jakarta, Indonesia.  Using an exploratory study, 305 students responded on the close and open-ended questions in bullying quetioner. The sample was selected using cluster random sampling technique. Data was analysed by the frequency of distribution to describe the extent to which bullying exists in university context. The finding showed that 19.34% participants have experienced as being bullied, 58,36% as bystanders and 16.72 % participants admitted as the bully. Direct and verbal bullying is the most frequently used of bullying.  The situation of bullying occurred is when the students were gathering with peer group (57,14%). Most of the victims of bullying chose a passive response in handling the bully and did not any attempt to help-seeking to stop bullying.  The percentages of being bullied in this study can be considered higher than other studies. This finding indicated that bullying in higher education still exists. The implication of this study suggests that the university has to take a formal regulation to stop bullying because the long-term negative impact of bullying on individual well-being.